Kesalahan Pemecahan Masalah Soal Cerita Pecahan pada Peserta Didik Sekolah Dasar: Systematic Literature Review (SLR) - Serlia Nurul Aizzah; Anesa Surya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Problem solving in mathematics, especially fraction word problems, is a challenge for elementary school students which can affect understanding of concepts. This research aims to examine the literature on the forms of errors made by students in solving fraction story problems and the factors that cause them. The method used is Systematic Literature Review (SLR), analyzing scientific articles published between 2015 and 2025, through the Google Scholar database with the keywords: "problem solving", "fraction word problems", and "mathematical errors". The research results show that the dominant types of student errors in problem solving include: (1) errors in understanding the problem; (2) errors in selecting surgery; (3) errors in calculating; (4) errors in interpreting answers. The causal factors include: (1) lack of understanding of the concept of fractions; (2) low reading ability; (3) limited problem solving strategies. The teacher's role in providing scaffolding and selecting a contextual approach is very important to reduce student errors. Thus, learning intervention based on error diagnosis is an important step to increase the effectiveness of solving fraction story problems in elementary school students.Pemecahan masalah dalam matematika, khususnya pada soal cerita pecahan, menjadi tantangan bagi peserta didik sekolah dasar yang dapat memengaruhi pemahaman konsep. Penelitian ini bertujuan untuk mengkaji literatur tentang bentuk-bentuk kesalahan yang dilakukan peserta didik dalam memcahkan masalah soal cerita pecahan serta faktor-faktor penyebabnya. Metode yang digunakan adalah Systematic Literature Review (SLR) artikel-artikel ilmiah yang dianalisis dipublikasikan antara tahun 2015 hingga 2025, melalui database Google Scholar dengan kata kunci: "problem solving", "fraction word problems", dan "mathematical errors". Hasil penelitian menunjukkan bahwa jenis kesalahan peserta didik dalam pemecahan masalah yang dominan meliputi: (1) kesalahan dalam memahami masalah; (2) kesalahan dalam memilih operasi; (3) kesalahan dalam melakukan perhitungan; (4) kesalahan dalam menafsirkan jawaban. Faktor penyebabnya antara lain: (1) kurangnya pemahaman konsep pecahan; (2) rendahnya kemampuan membaca; (3) keterbatasan strategi pemecahan masalah. Peran guru dalam memberikan scaffolding dan pemilihan pendekatan kontekstual sangat penting untuk mengurangi kesalahan peserta didik. Dengan demikian, intervensi pembelajaran berbasis diagnosis kesalahan menjadi langkah penting untuk meningkatkan efektivitas pemecahan masalah soal cerita pecahan pada peserta didik sekolah dasar.